Utility of contrast enhanced ultrasound (CEUS) in penile trauma - Miguel A. Gómez-Bermejo; Dean Y. Huang; Michele Bertolotto; Paul S. Sidhu (Insights into Imaging, 2023)
Abstract Penile traumatic injuries are rare with potentially severe consequences, with clinical assessment challenging due to pain and swelling. Ultrasound is the primary imaging modality for assessing the penis. It has a high spatial resolution and rapid availability and is portable. Contrast enhanced ultrasound is an advanced ultrasound technique that adds real-time dynamic vascular imaging safely, increasing diagnostic precision and confidence, allowing for better therapeutic management of traumatic penile injuries. Contrast enhanced ultrasound helps to delineate the extent of a haematoma, distinguishing this from the herniated corpus cavernosum, detecting the point of rupture of the tunica albuginea, showing vascular abnormalities, localising a dislocated penis and determining penile viability. The integrity of the urethra may be assessed with intracavitary contrast enhanced ultrasound. Additionally, contrast enhanced ultrasound allows monitoring of the response to endovascular and surgical treatment. This review aims to detail the anatomy and pathogenesis of penile trauma, to give guidance on optimising the contrast enhanced ultrasound technique and to obtain diagnostic examinations. Illustration of the spectrum of aspects of penile trauma will be complemented with a literature review. Critical relevance statement Contrast enhanced ultrasound is a safe and efficient imaging modality that allows for highly accurate diagnoses, helping achieve more successful and conservative treatments of penile trauma complications. Key points • Ultrasound is an accurate and safe imaging test for penile trauma. • CEUS adds dynamic vascular imaging in real-time increasing diagnostic confidence. • CEUS can delineate penile haematomas, locate fractures and demonstrate vessel integrity. • CEUS potentially allows for more conservative treatment of penile trauma complications. Graphical Abstract